2018
DOI: 10.1155/2018/5692962
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ginger (Zingiber officinale Roscoe) on Type 2 Diabetes Mellitus and Components of the Metabolic Syndrome: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials

Abstract: Objective This article aims to assess the effects of ginger (Zingiber officinale Roscoe) on type 2 diabetes mellitus (T2DM) and/or components of the metabolic syndrome (MetS). Methods Electronic literature was searched in PubMed, Embase, the Cochrane Library, Chinese Biomedical Database, China National Knowledge Infrastructure, and Wanfang Database from inception of the database to May 19, 2017, and supplemented by browsing reference lists of potentially eligible articles. Randomized controlled trials on resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 55 publications
3
73
0
12
Order By: Relevance
“…The regulatory impact of ginger on the glucose level has been demonstrated in the short and long term. A meta‐analysis performed by Zhu et al () showed that ginger significantly decreases fructose bisphosphatase and HbA1c, which indicates the long‐term effect of ginger on lowering blood sugar levels.…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory impact of ginger on the glucose level has been demonstrated in the short and long term. A meta‐analysis performed by Zhu et al () showed that ginger significantly decreases fructose bisphosphatase and HbA1c, which indicates the long‐term effect of ginger on lowering blood sugar levels.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Chen et al conducted an SR-MA of oral ginger intake and found that ginger could effectively control menstrual pain in dysmenorrhea [11]. Another SR-MA study revealed that ginger improved lipid profiles and benefited the glucose control, insulin sensitivity, and glycosylated hemoglobin of type 2 diabetes mellitus [12]. In addition, ginger's potency has been regularly proposed in arthritis, gastric dysfunction, and cancers [6,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, ginger roots (rhizomes) are widely used as a food spice (Eliopoulos, ). In addition, it is commonly used in traditional medicine because of its inherited and evidence‐based health benefits in wide‐range of diseased conditions/disorders such as cancers (Chen et al, ; Saha et al, ; Salafzoon, Mahmoodzadeh Hosseini, & Halabian, ), diabetes (Al Hroob, Abukhalil, Alghonmeen, & Mahmoud, ; Zhu, Chen, Song, Wang, & Sun, ), cardiovascular disease (Liu et al, ; Nicoll & Henein, ), male infertility (Banihani, ; Hosseini et al, ), ulcer (Liu et al, ; Wang et al, ), depression (Kukula‐Koch et al, ), rheumatoid arthritis (Funk, Frye, Oyarzo, & Timmermann, ), Alzheimer (Cuya, Baptista, Franca, & T., ) and nonalcoholic fatty liver disease (Sahebkar, ). In actual fact, the impact of ginger on human health is attributable to its potent bioactive properties such as antioxidant (Danwilai, Konmun, Sripanidkulchai, & Subongkot, ; Masuda, Kikuzaki, Hisamoto, & Nakatani, ), anti‐inflammatory (Jeena, Liju, & Kuttan, ), immuno‐modulatory (Ali, Blunden, Tanira, & Nemmar, ), antimicrobial (Park, Bae, & Lee, ) and anti‐tumorigenic properties (Ali et al, ).…”
Section: Introductionmentioning
confidence: 99%